2015
DOI: 10.35790/ecl.3.2.2015.8436
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Kadar Asam Urat Pada Subyek Obes Dan Non-Obes Di Fakultas Kedokteran Universitas Sam Ratulangi Manado

Abstract: Uric acid is the end product of purine metabolism. Circulating uric acid in the human body is produced by the body (endogenous uric acid) as well as derived from food (exogenous uric acid). Normal serum uric acid level is <7.0 mg / dL in men and <6.0 in women. Obesity can be defined as excess body fat. One of the markers used for body fat content is body mass index (BMI). This study aimed to compare the levels of uric acid in obese and non-obese subjects. This was an analytical study with a cross section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
5
0
3
Order By: Relevance
“…Similar studies show that high uric acid levels (hyperuricemia) is not only experienced by obese subjects but also in the non-obese. This may be due to genetic factors that contribute to elevated uric acid levels and reduced physical activity (Rau, Ongkowijaya, & Kawengian, 2015). Another study found their high levels of uric acid in the respondents overweight and obesity with the possible result of a decrease in renal excretion of uric acid due to insulin resistance and hyperinsulinemia occurring in the state of overweight and obesity (Karimba, Kaligis, and Purwanto, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Similar studies show that high uric acid levels (hyperuricemia) is not only experienced by obese subjects but also in the non-obese. This may be due to genetic factors that contribute to elevated uric acid levels and reduced physical activity (Rau, Ongkowijaya, & Kawengian, 2015). Another study found their high levels of uric acid in the respondents overweight and obesity with the possible result of a decrease in renal excretion of uric acid due to insulin resistance and hyperinsulinemia occurring in the state of overweight and obesity (Karimba, Kaligis, and Purwanto, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It means that the condition of obesity is indicated by abdominal circumference above the normal limit, and this increases the risk of hyperuricemia. 31 …”
Section: Resultsmentioning
confidence: 99%
“…Oleh karena itu, keadaan hiperinsulinemia dapat menyebabkan terjadinya peningkatan reabsorpsi asam urat yang akan menyebabkan hiperurisemia (14). Penelitian ini juga sesuai dengan studi sebelumnya di Manado yang menyatakan bahwa rerata kadar asam urat pada kelompok obesitas lebih tinggi secara bermakna dibandingkan kelompok non obesitas (15). Prevalensi huperurisemia juga lebih tinggi pada anak-anak dengan berat badan berlebih dan obesitas (17), sedangkan pada orang dewasa, peningkatan kadar asam urat sering ditemui pada orang dengan sindrom metabolik yang biasanya mempunyai berat badan berlebih, menderita hipertensi, dan mengalami resistensi insulin (16).…”
Section: Hubungan Obesitas Dengan Kejadian Hiperurisemiaunclassified